THE RELATIONSHIP BETWEEN SOCIAL ECONOMY AND PEER SUPPORT WITH VEGETABLES AND FRUIT CONSUMPTION BEHAVIORS AMONG VOCATIONAL STUDENT - Rinawati - tarigan (Alta Dharma Publisher, 2019)
Adolescent generally undergo changes in their lifestyle, including their consumption pattern.. Consumption of vegetables and fruit in adolescents is very important to support growth and good health status, if teenagers consume less vegetables and fruits are at risk of experiencing degenerative diseases that usually appear in adulthood. One of the problems in the juvenile phase is the lack of consumption of vegetables and fruits which are influenced by internal and external factors. Several factors related to the adequacy of vegetable and fruit consumption in adolescents include: characteristics, socioeconomic, and social support (family and peers). The research problem is how is the socio-economic relationship with the consumption of vegetables and fruits. The aim of the study was to examine socio-economic relations with consumption of vegetables and fruit students. This research is quantitative using a cross-sectional research design. The study was conducted at the State Vocational School 1 Percut Sei Tuan in Deli Serdang District. The samples were all students of class X and class XI Department of Software Engineering State Vocational High School 1 Percut Sei Tuan Deli Serdang Regency in 2018 amounting to 97 people. Data collection tool uses a questionnaire. The test used is chi-square (bivariate). The chi-square test results show that there is no a relationship between socioeconomic with vegetable consumption (p>0.05), whereas peer support there is relationship with vegetable consumption (p<0.05) and there is a relationship between socioeconomic (income household permonth, pocket money, vegetable available) and peer support with fruit consumptio (p<0.05). Researchers suggest that families, especially parents, continue to control adolescents, including peers and in terms of consumption of vegetable and fruit both at home and outside the home.